FEATURES OF MANAGEMENT OF TECHNOLOGICAL PROCESSES AT THE AIRPORT - Тамаргазін, О.А.; Ліннік, І.І. (Science-based technologies, 2017)
In this article we have considered the concept of process management from the position of usage when analyzing the functioning of a modern airport, as a complex organizational-technical systems. The definition of the main categories of management theory that are used in the creation of the information field at the airport for the purpose of adapting management processes in various production situations. The role and place of the decision makers in the management of elements of the airport upon reaching, both internal and external production goals. The sequence of actions of decision-makers, is regarded as from the standpoint of the daily work of the airport, and from the standpoint of the formation of the control actions in emergency situations. At the same time, the governance process at the airport is considered, taking into account its cyclical nature and the need to perform a series of tasks to achieve the goals in parallel.